Biochemical engineering and biotechnology - Najafpour, Ghasem D. (Elsevier, 2007)
Extensive application of bioprocesses has generated an expansion in biotechnological knowledge, generated by the application of biochemical engineering to biotechnology. Microorganisms produce alcohols and acetone that are used in industrial processes. The knowledge related to industrial microbiology has been revolutionized by the ability of genetically engineered cells to make many new products. Genetic engineering and gene mounting has been developed to enhance industrial fermentation. Ultimately, these bioprocesses have become a new way of developing commercial products. Biochemical Engineering and Biotechnology demonstrates the application of biological sciences in engineering with theoretical and practical aspects to enhance understanding of knowledge in this field. The book adopts a practical approach, showing related case studies with original research data. It is an ideal text book for college and university courses, which guides students through the lectures in a clear and well-illustrated manner. Demonstrates the application of biological sciences in engineering with theoretical and practical aspects. Unique practical approach, using case studies, detailed experiments, original research data and problems and possible solutions. Gives detailed experiments with simple design equations and the required calculations.